INS AND OUTS OF AZURE VMWARE SOLUTION : deploy, configure and manage an azure vmware solution ... environment - JELLOW, KEVIN (PACKT Publishing Limited, 2023)
Manage VMware workloads in Azure VMware Solution and enable hybrid connectivity between on-premises datacenters and Azure with this extensive guide focusing on best practices and use cases Key Features Extend or migrate your existing VMware environment to Azure VMware Solution smoothly Discover best practices that are based on real customer experiences Join the cloud revolution by conducting the most suitable migration for your workloads Book Description Organizations over the world are migrating partially or fully to the cloud, but with the whole slew of providers, tools, and platforms available, knowing where to start can be quite challenging. If you know Microsoft Azure VMware Solution, you know it is the quickest way to migrate to the cloud without needing application modernization or rework. You can retain the same VMware tools to manage your environment while moving to Azure. But how does it work? The Ins and Outs of Azure VMware Solution has the answer. This high-level, comprehensive yet concise guide to Azure VMware Solution starts by taking you through the architecture and its applicable use cases. It will help you hit the ground running by getting straight to the important steps: planning, deploying, configuring, and managing your Azure VMware Solution instance. You'll be able to extend your existing knowledge of Azure and VMware by covering advanced topics such as SRM and governance, setting up a hybrid connection to your on-premises datacenter, and scaling up using disk pools. By the end of the VMware book, you'll have gone over everything you need to transition to the cloud with ease using Azure VMware Solution. What you will learn Get to grips with the overall architecture of Azure VMware Solution Discover Enterprise-scale for Azure VMware Solution Deploy an Azure VMware private cloud successfully Deploy and configure HCX in Azure VMware Solution Configure NSX-T network segments with the NSX-T Manager Configure internet access, traffic inspection, and storage for AVS Integrate Azure VMware Solution with Azure-native services Use governance to improve your cloud portfolio Who this book is for This book is for VMware administrators, cloud solutions architects, and anyone interested in learning how to deploy and configure an AVS environment in Azure. Technology leaders who want to get out of the datacenter business or expand their on-premises datacenter into Microsoft Azure will also find this book useful. Familiarity with VMware solutions and a basic understanding of Azure networking is necessary to get started with this book.